Analysis Of The Influence Of Artificial Intelligence Deepfakes From The Perspective Of Legal Science - Inka Verandera Nugraha (Consensus : Jurnal Ilmu Hukum, 2024)
In its urgency, AI itself has developed rapidly with the aim of facilitating the acquisition of information by humans in a more expeditious and succinct manner. However, the creation of a system entails a duality of positive and negative consequences. The benefits of AI include the potential to streamline human workflows, provide assistance, and address queries. However, as with any technology, there are also risks and challenges. One such challenge is the emergence of deepfake, a phenomenon where artificial intelligence is used to create realistic fake videos. Deepfake is a video that employs artificial intelligence to portray a person saying and doing things that did not occur in real life. To illustrate, a face swap can be performed in a way that leaves minimal evidence of manipulation on the video. Accordingly, the author investigates the potential for leveraging existing legal frameworks to hold perpetrators of deepfake criminally liable. The research method employed is the normative legal research method. This involves the collection and discussion of positive legal rules in Indonesia and the European Union as a source of primary legal material, as well as related literature as a source of secondary legal material. The results demonstrate that, given that deepfake is an AI that uses electronic data or information, the PDP Law and GDPR are pertinent to the examination of regulations pertaining to the prohibition of AI manipulation for the purpose of misinformation, disinformation, or fraud and the creation of fake news in the cyber world.